Efficacy and safety of innate and adaptive immunotherapy combined with standard of care in high-grade gliomas: a systematic review and meta-analysis - Guo, Baofeng; Zhang, Shengnan; Xu, Libo; Sun, Jicheng; Chan, Wai-Lun; Zheng, Pengfei; Zhang, Jinnan; Zhang, Ling (Frontiers in Immunology, 2023)
Background Malignant glioma is the most common intracranial malignant tumor with the highest mortality. In the era of immunotherapy, it is important to determine what type of immunotherapy provides the best chance of survival. Method Here, the efficacy and safety of immunotherapy in high-grade glioma (HGG) were evaluated by systematic review and meta-analysis. The differences between various types of immunotherapy were explored. Retrieved hits were screened for inclusion in 2,317 articles. We extracted the overall survival (OS) and progression-free survival (PFS) hazard ratios (HRs) as two key outcomes for examining the efficacy of immunotherapy. We also analyzed data on the reported corresponding adverse events to assess the safety of immunotherapy. This study was registered with PROSPERO (CRD42019112356). Results We included a total of 1,271 patients, of which 524 received a combination of immunotherapy and standard of care (SOC), while 747 received SOC alone. We found that immunotherapy extended the OS (HR = 0.74; 95% confidence interval [CI], 0.56−0.99; Z = −2.00, P = 0.0458 < 0.05) and PFS (HR = 0.67; 95% CI, 0.45−0.99; Z = −1.99, P = 0.0466 < 0.05), although certain adverse events occurred (proportion = 0.0773, 95% CI, 0.0589-0.1014). Our data have demonstrated the efficacy of the dendritic cell (DC) vaccine in prolonging the OS (HR = 0.38; 95% CI, 0.21−0.68; Z = −3.23; P = 0.0012 < 0.05) of glioma patients. Oncolytic viral therapy (VT) only extended patient survival in a subgroup analysis (HR = 0.60; 95% CI, 0.45−0.80; Z = −3.53; P = 0.0004 < 0.05). By contrast, immunopotentiation (IP) did not prolong OS (HR = 0.69; 95% CI, 0.50−0.96; Z = −2.23; P = 0.0256). Conclusion Thus, DC vaccination significantly prolonged the OS of HGG patients, however, the efficacy of VT and IP should be explored in further studies. All the therapeutic schemes evaluated were associated with certain side effects. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=112356.